Implikasi Hukum Perlindungan Data Pribadi dalam Era Digital (Jurnal Begawan Hukum (JBH), 2024)
In the ever-growing digital era, protecting personal data is becoming increasingly important. This article discusses the legal implications related to the protection of personal data in the digital environment. As information and communications technology advances, the collection, storage, and use of personal data has become central to many aspects of life, including business, government, and personal life. The laws governing these issues are becoming increasingly complex as challenges arise, such as data breaches, online privacy, and regulatory changes. This article analyzes the applicable legal framework, including existing personal data protection regulations, such as the European Union's GDPR, and their impact on organizations, individuals and society as a whole. The research also addresses emerging new challenges in personal data protection, such as the use of artificial intelligence and advanced data analytics. These legal implications are very relevant in a global context and require special attention in efforts to safeguard individual rights and regulate the ethical use of personal data.